Legal Enforceability of Preliminary Sale Agreements on Mortgaged Strata Title Units - Bella, Yoshua; Noor, Aslan; Chandra, Teddy (Magister Kenotariatan Universitas Pasundan, 2025)
This study examines the legal status and enforceability of Preliminary Sale and Purchase Agreements, in the context of mortgaged strata title units under Indonesian property and contract law. While the agreement serve as binding commitments between developers and buyers, they do not effectuate ownership transfer and are not publicly registered, rendering them legally subordinate to mortgage encumbrances that are recorded and enforceable as real rights. The research applies a normative-juridical method, supported by doctrinal and comparative legal analysis, to assess the hierarchy between personal contractual rights and secured creditor claims. Findings reveal that consumers who enter into of Preliminary Sale and Purchase Agreements, for units still burdened by mortgages face significant legal uncertainty, particularly in cases of developer default. The study further evaluates the adequacy of Indonesia's consumer protection framework, highlighting the persistence of exploitative clauses in of Preliminary Sale and Purchase Agreements, and the absence of institutional safeguards. To reconcile the imbalance between buyers and financial institutions, the paper proposes regulatory reforms, including the mandatory registration of PPJBs, standardized contract terms, and strengthened disclosure obligations. These recommendations aim to enhance legal certainty, uphold the principles of pacta sunt servanda, and ensure more equitable outcomes in Indonesia's increasingly complex vertical housing market.